2017
DOI: 10.18632/oncotarget.20484
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of traditional oncomiRs in plasma of breast cancer patients

Abstract: Deregulated expression of microRNAs has the oncogenic or tumor suppressor function in cancer. Since miRNAs in plasma are highly stable, their quantification could contribute to more precise cancer diagnosis, prognosis and therapy prediction. We have quantified expression of seven oncomiRs, namely miR-17/92 cluster (miR-17, miR-18a, miR-19a and miR-20a), miR-21, miR-27a and miR-155, in plasma of 137 breast cancer (BC) patients. We detected down-regulation of six miRNAs in patients with invasive BC compared to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 65 publications
5
37
1
1
Order By: Relevance
“…These data are in agreement with a previous report by Nunes et al (2015) which validated the down-regulation of these miRNAs in early diabetes and retinal neovascularization in vivo, together with locally increased VEGF (Nunes et al, 2015). Additionally, miR-20a was predicted to act as a tumor suppressor and was found significantly down-regulated in the serum of advanced breast cancer patients (Jurkovicova et al, 2017). Moreover, miR-20b was able to regulate VEGF expression in a rat model of DR, both in vitro and in vivo (Qin et al, 2016).…”
Section: Choroid-retinal Endothelial Cells Monolayer After Interleukisupporting
confidence: 93%
“…These data are in agreement with a previous report by Nunes et al (2015) which validated the down-regulation of these miRNAs in early diabetes and retinal neovascularization in vivo, together with locally increased VEGF (Nunes et al, 2015). Additionally, miR-20a was predicted to act as a tumor suppressor and was found significantly down-regulated in the serum of advanced breast cancer patients (Jurkovicova et al, 2017). Moreover, miR-20b was able to regulate VEGF expression in a rat model of DR, both in vitro and in vivo (Qin et al, 2016).…”
Section: Choroid-retinal Endothelial Cells Monolayer After Interleukisupporting
confidence: 93%
“…On the contrary, Wang et al [22] found that serum miR-155 overexpression correlated with ER/PR-negative status. Similar discrepancies were found when other tumour parameters were assessed: Swellam et al [35] and Wang et al [22] found that serum miR-155 correlated with grade, whereas Jurkovicova et al [26] and Anwar et al [37] did not find this correlation. Regarding the TNM stage, five studies [25,27,29,30,35] reported that increased expression of circulating miR-155 was significantly associated with advanced stage, whereas the other four studies [23,30,31,37] did not find any correlations.…”
Section: Circulating Mir-155 Versus Patient-and Tumour-related Prognomentioning
confidence: 60%
“…Regarding tumour size, Answar et al [37] assessed the relationship between circulating miR-155 and tumour size, finding a significantly higher miR level in BC patients with tumours larger than 5 cm, whereas Jukovicova et al [26] and Soleimanpour et al [31] found no significant association. Concerning tumour hormonal status, Swellam et al [35] and Jurkovicova et al [26] did not find any significant correlations among serum and plasma miR-155 and ER/PR status, respectively. On the contrary, Wang et al [22] found that serum miR-155 overexpression correlated with ER/PR-negative status.…”
Section: Circulating Mir-155 Versus Patient-and Tumour-related Prognomentioning
confidence: 99%
“…In patients with recurrent breast cancer, miR-17-5p is upregulated in tumor tissues and significantly downregulated in serum as one of the exosomal miR-NAs [36]. In contrast, statistically significant reductions in the levels of miR-17 and miR-19a in plasma have been observed between early and advanced stages of breast cancer [37]. With regard to the expression of miR-17-5p in GC, the majority of studies considered that this miRNA is upregulated in GC tissues [28][29][30][31][38][39][40].…”
Section: Discussionmentioning
confidence: 98%